Synthesis of pyrido[2,3-d]pyrimidines via palladium-catalyzed coupling reaction followed by electrocyclic reaction - Rho, KY; Kim, JH; Kim, SH; Yoon, CM (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
Pyrido[2,3-d]pyrimidines (5a-h) were regioselectively synthesized by the reaction of 5-iodo-6-(dimethylaminomethylene)amino-1,3-dimethyluracil(3), which was prepared from the reaction of 6-amino-1,3-dimethyluracil with dimethylformamide dimethyl acetal followed by iodination, with various olefins (4a-h) in the presence of a catalytic amount of Pd(OAc)(2), Cul, and K2CO3 in DMF at 100 degrees C.
Keywords: QUINAZOLINES